Minimization of prediction errors during cerebral embryogenesis and the emergence of agency - Wright, James Joseph; Bourke, Paul David (Frontiers in Systems Neuroscience, 2025)
A theory of self-organization in the central nervous system is described, proposing that additive and dissipative synaptodendritic summation leads to synchronous oscillation as the equilibrium state, thereby underpinning a primary mechanism of prediction error minimization. As a consequence, synaptic connections become arranged in mirror-symmetric paired patterns, wherein exchanges of synaptic flux within each pattern form coupled spatial eigenmodes. The mirror-reflection axis between each pair functions as a Markov blanket that maintains excitatory–inhibitory equilibrium, while multiway exchanges among mirror pairs converge toward overall error minimization and mutual organization. The primary organization of this type is evident in the spinal cord. During cortical embryogenesis, connections develop in topographies interpretable as mirror reflections with broken symmetry, aligning along the radial and circumferential axes of cortical growth, as described by the Structural Model, and subsequently manifest at the millimetric scale throughout the cortex. The proposed framework integrates a diverse range of experimental data and provides an explanatory basis for how generative models with agency can emerge through both species evolution and individual learning.